Implications Project-Based Learning (PjBL) Assisted Flipped Classroom on Critical Thinking Ability of Gender-Based Students on the Concept of Water Pollution - Indri Puspitasari; Aa Juhanda; Jujun Ratnasari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Students' critical thinking abilities are still low for both female and male students. Initial data results obtained from the pretest, female students with a percentage of 35% and male students with a percentage of 27%. The aim of this research is to determine the effect of the project-based learning model assisted by the flipped classroom on gender-based junior high school students' critical thinking abilities on the concept of water pollution. This research uses a quantitative type of research with a sample of class VII students at SMPN 6 Sukabumi City, even semester of the 2022/2023 academic year. The instrument used is a critical thinking skills test. The results obtained show that the average posttest score for female students is 74.2 ± 12.6 and male students is 69.0 ± 11.0. Both of them have increased from the pretest and posttest, but the female scores are superior. The percentage per ability indicator based on gender in indicators 1,2,3 shows that women are superior to men. However, in indicators 4 and 5, women and men are the same. Overall, the data shows that there is no significant difference in learning using the Project Based Learning model assisted by Flipped Classroom between female and male students. However, based on indicators, female students are superior to male students.